Eksistensi Dampak Yang Mempengaruhi Faktor Keinginan Mahasiswa Menggunakan E-Money - Gumilang, Risa Ratna (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
The size of the use of e-money does not affect students using e-money because the use of e-money is the same as cash / cash (the function is the same). Sig value e-money convenience variable significantly influences student interest in using e-money. The easier e-money is used, the higher the interest of students using it. Sig value E-money security affects the interest of students using e-money. The higher the security of e-money, the higher the interest of students in using e-money.